The use of ai in learning English: a comparative study between Moroccan and Indonesian undergraduate students from the English department - KHOUDRI, Insaf; ZERIOUH, Mohammed; FAUZAN, Umar; KHOUDRI, Abderrafiî (Edelweiss Applied Science and Technology, 2024)
It is generally understood that people’s attitudes influence and shape their behavior. However, there is still a gap in knowledge regarding how undergraduate students from different countries perceive AI in learning English. This paper aims to compare two groups of undergraduate students from the English departments of Morocco and Indonesia. To achieve this, an online structured questionnaire was administered to 240 undergraduate students from these two countries. Data collected were analyzed using SPSS version 25 and the Mann-Whitney test. The findings revealed that both groups are optimistic about using AI for learning English. They utilize AI tools for feedback, engagement, motivation, personalized learning, and autonomy. However, there is a disparity in how each group uses AI for translation. Additionally, participants expressed concerns about AI related to privacy and security, overreliance and lack of responsibility, critical thinking and creativity issues, and plagiarism. The study suggests that AI can be both beneficial and detrimental. Incorporating AI into the classroom is essential for improving students’ AI literacy and enhancing their academic and language skills. A balanced approach to AI use involves not only providing students with diverse AI tools suited to their academic needs but also raising awareness about the ethical issues associated with AI.